Penerapan Platform Daya Dukung Dan Manajemen Pengunjung Dengan Pembuatan Papan Informasi Berbasis Ecobrick - Auda Nuril Zazilah; Reni Nur Jannah; Firda Rachma Amalia; Nurhalimah Nurhalimah; Rudi Tri Handoko (Journal of Community Development, 2025)
In understanding the sustainability of Blimbingsari Beach, community service activities are carried out at Blimbingsari Beach. Blimbingsari Beach is famous for its grilled fish culinary and has a very strategic location close to Blimbingsari Banyuwangi Airport. The problem at Blimbingsari Beach is the lack of optimal management in arranging the number of tourist visits which is not balanced with the capacity of the beach area, environmental factors and management factors. The second problem is related to beach cleanliness which contradicts the culinary of grilled fish which is a characteristic of Blimbingsari Beach. The purpose of this service activity is to provide understanding to the Tourism Awareness Group (POKDARWIS) in managing visitors and provide ecobrick making training to POKDARWIS and the surrounding community which can be a solution in overcoming both existing problems. The methods used in this activity start from coordination, socialization, training implementation to evaluation. The result of the first problem is in the form of understanding and applying the tourist attraction carrying capacity platform to find out the maximum number of tourist visits at Blimbingsari Beach so that visitors still get satisfaction and continue to pay attention to environmental factors. This is in accordance with the concept of sustainable tourism. The result of the second problem is the ability of POKDARWIS and the surrounding community to make ecobricks and the existence of an ecobrick-based tourist information board placed on Blimbingsari Beach.